Maddalena and the dark - Fine, Julia (Flatiron Books, 2023)
"For fans of My Brilliant Friend and Mexican Gothic, Julia Fine's Maddalena and the Dark is a novel set in 18th-century Venice at a prestigious music school, about two girls drawn together by a dangerous wager..."--